Find the sum of all integer values of satisfying the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let a = 3 z + 2 and b = 3 2 − z . Then, we know that a 2 + 3 b 2 = 4 a b . ( a − b ) ( a − 3 b ) = 0 ⟹ a = b or a = 3 b . By substituting back the values, we obtain 3 z + 2 = 3 2 − z or 3 z + 2 = 3 ( 3 2 − z ) . Cubing both sides of the equation results in z + 2 = 2 − z or z + 2 = 2 7 ( 2 − z ) . ∴ z = 0 or z = 1 7 6 , the required integer solution is z = 0 .